Wastelanding Arabia: America's 'Garden of Eden' in Al Kharj, Saudi Arabia. (July 2022) - Koch, Natalie
Abstract: In the late 1930s, the American oil company Aramco helped Saudi Arabia's King Ibn Saud develop his royal farm outside Riyadh. On the king's request, Aramco introduced new technology to tap the Al Kharj region's rich aquifer water and establish vast fields of wheat, alfalfa, and other water-intensive crops. Saudi Arabia's aquifers have since been pumped dry in service of the 'Garden of Eden' idyll promised by American advocates, who boasted of their ability to reclaim thousands of acres of 'desert wasteland.' This article draws on Traci Voyles' formulation of 'wastelanding' to interrogate the agricultural spectacle of Al Kharj in the 1930s–50s. The project was an early exemplar what came to be an established pattern of wastelanding Arabia, built on the unsustainable use of groundwater and social inequalities to create an 'Eden' in the desert. Agricultural wastelanding has unique spatial and temporal dimensions that set it apart from other extractive industries, like the uranium mining that Voyles examines in Diné lands. But as this article shows, desert greening projects draw on and produce similar structures of social and environmental violence – with America's 'Garden of Eden' in central Arabia being just one case among many of wastelanding across space and time. Highlights: Examines spectacular desert agriculture projects as a form of 'wastelanding'. Presents the history of American involvement in developing the Al Kharj farm in Saudi Arabia. Traces the role of 'Garden of Eden' narratives moving from the United States to the Arabian Peninsula.